Early Results From the ‘Diggers to Veterans’ Longitudinal Study of Australian Men who Served in the First World War. Short- and Long-Term Mortality of Early Enlisters - Janet McCalman; Rebecca Kippen; Joan McMeeken; John Hopper; Michael Reade (Historical Life Course Studies)
As the world marks the centenaries of the First World War, we still know remarkably little about the life course effects of military service. This paper reports on the first iteration of a cradle-to-grave dataset of men who enlisted and served overseas in the First World War from the state of Victoria, Australia. It examines mortality during military service and in civilian life and finds that mortality in both cases was strongly correlated with individual characteristics. Tall men and young single men were more likely to die in the war. In civilian life, mortality followed closely the pattern for Australian men, and was again highly correlated with individual characteristics and social class.